1991
DOI: 10.1177/001316449105100425
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Contribution of an Interview to College Admissions

Abstract: A study was conducted to investigate possible redundancies between interviewer judgments and applicant paper credentials, and the incremental contribution of interviewer judgments to the prediction of selection decisions and future performance. The motivation and oral communication of college applicants were assessed in a face-to-face interview and on the basis of paper credentials. Interviewer judgments provided unique information about applicants and were significantly related to grade point average (GPA). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…They are often related to both knowledge and personality constructs (Cortina et al, 2000), partly because the interview can assess a wide range of constructs (Huffcutt et al, 2001). The incremental validity research evidence is also mixed, with some studies finding no incremental validity (Campion, Pursell, & Brown, 1988; Shahani, Dipboye, & Gehrlein, 1991; Walters, Miller, & Ree, 1993) and other studies finding incremental validity (Campion, Campion, & Hudson, 1994; Latham & Sue‐Chan, 1999).…”
Section: Views On Selection In Team Settingsmentioning
confidence: 99%
“…They are often related to both knowledge and personality constructs (Cortina et al, 2000), partly because the interview can assess a wide range of constructs (Huffcutt et al, 2001). The incremental validity research evidence is also mixed, with some studies finding no incremental validity (Campion, Pursell, & Brown, 1988; Shahani, Dipboye, & Gehrlein, 1991; Walters, Miller, & Ree, 1993) and other studies finding incremental validity (Campion, Campion, & Hudson, 1994; Latham & Sue‐Chan, 1999).…”
Section: Views On Selection In Team Settingsmentioning
confidence: 99%
“…The incremental value of the social competence dimension over cognitive ability is a little lower, but still high (Nagelkerke's Δ R 2 = 6%). This finding contradicts Shahani, Dipboye, and Gehrlein (, see also Campion et al, ) who argued that the interview was just a further instrument to measure cognitive ability. Research by Huffcutt, Conway, Roth, and Klehe () found out that concerning validity, for highly complex jobs, behavioral description interviews (which focus on the evaluation of the candidate's past behavior relevant to the target position) should be preferred to situational structured interviews (which focus on evaluation of reactions to hypothetical job situations) confirming the approach described in this article.…”
Section: Discussionmentioning
confidence: 70%
“…The McMaster's admissions interview did not predict licensure examination performance except in the LMCC (Licentiate of the Medical Council of Canada) Part II (Communication) ( r = 0.24, P < 0.05), the same variance predicted by undergraduate GPA and subjective ratings of applicants' essays 4 . Similarly, a private undergraduate university found admissions interviews predicted undergraduate GPA ( r = 0.10, P < 0.05), but that Scholastic Aptitude Test (SAT) verbal scores explained more variance and interviews explained none of the residual 5 . This may reflect poor measurement of non‐cognitive skills by LMCC tests and undergraduate grades, but there are published failures of interviews to predict plainly observable outcomes from non‐cognitive factors.…”
Section: Introductionmentioning
confidence: 83%
“…Nearly all medical school admissions departments use interviews to assess applicants' non‐cognitive skills 1,2 . Admissions departments value this information highly, 3 although it has low reliability and validity 3–5 . Medical school admissions departments rank the impact of interviews on selection decisions above undergraduate grade point average (GPA) and Medical College Admission Test (MCAT) scores, yet only 20% assess predictive validity and only 12% assess reliability 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation